Toward energy self-sufficiency in small municipal wastewater treatment plants: assessment of energy recovery potential, process economic balance, and greenhouse gas avoidance - Fernanda Amaral-Góis; Vinicius J. Silva; Renan C. Testolin; Ramaiana Radetski-Silva; Dilamara R. Scharf; Marcelo Poyer-Radetski; Wendell Pimentel-Almeida; Cleder A. Somensi; Rafael Ariente-Neto; Claudemir M. Radetski (Environmental Science and Pollution Research, 2026)
The objective of this study was to quantitatively assess the energy recovery potential from both biogas and the incineration of dewatered sludge, aiming to meet the energy demand of a small municipal wastewater treatment plant (MWTP) with a treatment capacity below 50 L s −1 . The energy potential of sludge incineration was characterized based on its gross calorific value, while energy production from biogas generated during the anaerobic digestion of municipal sludge was also evaluated. In addition, the feasibility of using the produced biogas for the thermal drying of dewatered sludge was analyzed. The results indicate that biogas utilization could generate 1462 kWh d −1 , corresponding to 83.17% of the total electricity consumption of the MWTP. Furthermore, the mass reduction achieved through sludge drying resulted in an annual cost savings of US$ 27,763 related to sludge disposal. The incineration of dried sludge could generate an additional 432.52 kWh d −1 . Overall, the combined energy recovery strategy could lead to a reduction of approximately 150 t CO 2 eq year −1 in greenhouse gas emissions due to methane avoidance at the studied MWTP. These findings suggest that such integrated approaches can encourage investments in MWTPs aimed at achieving energy self-sufficiency while enhancing environmental performance. Graphical abstract

Eco(geno)toxicity of the new commercial insecticide Platinum Neo, a mixture of the neonicotinoid thiamethoxam and the pyrethroid lambda-cyhalothrin - Felippe L. Dalpiaz; Rosane Laçoli; Nicolli Butzke-Souza; José R. Santin; Leticia Poyer-Radetski; Juliana A. Dallabona; Renan C. Testolin; Tito C.M. Almeida; Claudemir M. Radetski; Sylvie Cotelle (Environmental Pollution, 2024)

Climatic and biogeographic factors show contrasted effects on continental and volcanic ISARs - L. Cáceres-Polgrossi; F. Buldrini; V. Bruzzaniti; J. M. Fernández-Palacios; R. Testolin; P. Zannini; A. Chiarucci (Community Ecology, 2024)
Aim The study of islands biotas is fundamental to understand biodiversity patterns and process, both on evolutionary and ecological time scales. This study explores the influence of biogeographic and climatic factors on island species–area relationships (ISARs) in volcanic and continental islands, aiming to detect differences in slopes and intercepts between these island origins. Methods Data from 5049 vegetation plots on 58 Central Mediterranean Sea islands were collected from various sources. Islands were categorized as volcanic or continental based on their geological origin. area, isolation, maximum elevation, eccentricity, mean annual temperature and annual precipitation were calculated for each island. By using a moving window, we created groups of islands, and ISARs were fitted to each group using the Arrhenius power functions. Linear models and a permutation test were employed to examine how ISAR model parameters varied with the above-mentioned variables. Results While ISAR intercept values did not differ between island origins, volcanic islands showed higher ISAR slopes than continental islands. Whereas increasing island isolation and mean annual temperature increased ISAR intercepts on continental islands groups, it decreased on volcanic ones. Increasing annual precipitation decreased ISAR intercept on continental islands groups and increased on volcanic islands groups. Increasing island isolation, eccentricity and mean annual temperature increased the ISAR slope on volcanic islands groups while increasing annual precipitation decreased it. Increasing maximum elevation increased ISAR slope on continental islands groups. Main conclusions Our study provides evidence about the importance of island geological origin in determining the observed ISAR patterns. Biogeographic and climatic factors are pivotal in shaping species richness patterns on islands, exerting varying influences on both volcanic and continental islands.

Biogeography of orchids and their pollination syndromes in small Mediterranean islands - M. Lussu; P. Zannini; R. Testolin; D. Dolci; M. Conti; S. Martellos; A. Chiarucci (Journal of Biogeography, 2024)
Aims Despite the research on orchid in insular conditions, few studies are focused on the spatial distribution of their reproductive syndromes across complex insular systems. By using island species–area relationships (ISAR), we explore orchid biogeography in the Central Western‐Mediterranean islands. In this study, we aim to investigate variation in ISARs using orchid pollination mechanisms as proxies to establish permanent populations explaining how the c and z parameters of ISARs vary among island types and pollination strategies and defining the most influential factors in shaping orchids' distribution. Location Mediterranean Basin. Taxon Orchidaceae. Methods Checklist of native orchids was obtained for 112 islands of Central‐Western Mediterranean Basin. The Arrhenius power function () was used to fit ISARs for the total number of orchids as well as for functional groups defined by the pollination strategies, across different island types. We used GLM to investigate the relation between pollination syndromes with area and isolation as well as elevation, island origin, taxa richness of the source area and habitat diversity. Results We found that ISARs differ between continental and volcanic islands depending on isolation. The z ‐value was found to be higher for more specialized strategies while the c ‐value increases from autogamy to allogamy, supporting the role of these two parameters in understanding distributional dynamics. Distance from the mainland is a negative predictor for all the strategies except when deception is decoupled; island area is a positive predictor only for allogamic, deceptive and food deceptive strategies, while habitat diversity is a positive predictor for allogamic, rewarding and deceptive strategies. Main Conclusions Pollination syndromes contribute in explaining the distribution of orchids in insular conditions. Furthermore, we identified differences in ISARs across pollination syndromes in which the intercept increases when the pollination shifts from a generalist to a more specialized one.

Area, environmental heterogeneity, scale and the conservation of alpine diversity - George P. Malanson; Riccardo Testolin; Elizabeth R. Pansing; Borja Jiménez‐Alfaro (Journal of Biogeography, 2023)
Aim Area and environmental heterogeneity together explain most patterns of species diversity but disentangling their relative importance has been difficult. Here, we empirically examined this relationship and parsed their relative importance, and that of the heterogeneity—effective area trade‐off, at different spatial scales and in different spatial representations in simulations. Location Alpine grasslands of 23 mountain ranges of southern and central Europe. Taxon Vascular plants. Methods We developed metrics of climatic and edaphic heterogeneity, using principal components analyses and the shoelace algorithm, and added elevation range. We applied commonality analysis to partition the unique and shared explanation of the observed vascular plant species richness among selected metrics. A simulation was developed to separate the relative importance of area and heterogeneity at different extents and representations of spatial nestedness, and the heterogeneity—effective area trade‐off was evaluated by altering spatial discreteness. Results The explanation of the observed regional richness was shared by area and heterogeneity. The simulation revealed that heterogeneity was consistently more important, but less so among smaller areas. This qualitative pattern was maintained regardless of whether and how nestedness was represented. The heterogeneity–effective area trade‐off occurred in a few simulations of more discrete habitats. Main Conclusions Scale dependence may account for discrepancies among past empirical studies wherein environmental heterogeneity has usually outweighed area in the explanation of species richness; and it is not affected by nestedness. The potential heterogeneity–effective area trade‐off may be limited to locations where the environmental heterogeneity is quite discrete or if the added environment is beyond the niches of any species in the potential pool. The significant importance of area per se in small territories indicates that microrefugia, even with an unlikely full range of heterogeneity, will suffer local extinctions in the face of climate change.

Metronidazole Degradation by Physico-chemical and Advanced Oxidative Processes: Influence of pH and nTiO2-Functionalized Macroporous Support - Eric Sanches-Simões; Renan C. Testolin; Felipe M. Müller; Otto M. S. Gerlach; Wendell Pimentel-Almeida; Aline Dal Conti-Lampert; Albertina X. R. Corrêa; Gizelle I. Almerindo; Sergio Y. Gómez González; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Mesoscale refugia for European alpine grasslands based on climatic envelopes - George P. Malanson; Riccardo Testolin; Elizabeth R. Pansing; Borja Jiménez-Alfaro (Alpine Botany, 2022)

Post‐glacial determinants of regional species pools in alpine grasslands - Borja Jiménez‐Alfaro; Sylvain Abdulhak; Fabio Attorre; Ariel Bergamini; Maria Laura Carranza; Alessandro Chiarucci; Renata Ćušterevska; Stefan Dullinger; Rosario G. Gavilán; Gianpietro Giusso del Galdo; Nevena Kuzmanović; Paola Laiolo; et al. (Global Ecology and Biogeography, 2021)
Aim Alpine habitats support unique biodiversity confined to high‐elevation areas in the current interglacial. Plant diversity in these habitats may respond to area, environment, connectivity and isolation, yet these factors have been rarely evaluated in concert. Here we investigate major determinants of regional species pools in alpine grasslands, and the responses of their constituent species groups. Location European mountains below 50° N. Time period Between 1928 and 2019. Major taxa studied Vascular plants. Methods We compiled species pools from alpine grasslands in 23 regions, including 794 alpine species and 2,094 non‐alpines. We used species–area relationships to test the influence of the extent of alpine areas on regional richness, and mixed‐effects models to compare the effects of 12 spatial and environmental predictors. Variation in species composition was addressed by generalized dissimilarity models and by a coefficient of dispersal direction to assess historical links among regions. Results Pool sizes were partially explained by current alpine areas, but the other predictors largely contributed to regional differences. The number of alpine species was influenced by area, calcareous bedrock, topographic heterogeneity and regional isolation, while non‐alpines responded better to connectivity and climate. Regional dissimilarity of alpine species was explained by isolation and precipitation, but non‐alpines only responded to isolation. Past dispersal routes were correlated with latitude, with alpine species showing stronger connections among regions. Main conclusions Besides area effects, edaphic, topographic and spatio‐temporal determinants are important to understand the organization of regional species pools in alpine habitats. The number of alpine species is especially linked to refugia and isolation, but their composition is explained by past dispersal and post‐glacial environmental filtering, while non‐alpines are generally influenced by regional floras. New research on the dynamics of alpine biodiversity should contextualize the determinants of regional species pools and the responses of species with different ecological profiles.

Petroleum-contaminated soil: using sonolysis to improve mineralization and biodegradation potential of Fenton reaction and ozonolysis process - Renan C. Testolin; Luciana Mater; Ramaiana Radetski-Silva; Eric Sanches-Simões; Wendell Pimentel-Almeida; Gabriela T. Schmidt; Rafael Ariente-Neto; Albertina X. R. Corrêa; Cleder A. Somensi; Claudemir M. Radetski (Environmental Science and Pollution Research, 2021)

Ecotoxicity assessment of particulate matter emitted from heavy-duty diesel-powered vehicles: influence of leaching conditions - Albertina X. R. Corrêa; Renan C. Testolin; Mariana M. Torres; Sylvie Cotelle; Jean-Jacques Schwartz; Maurice Millet; Claudemir M. Radetski (Environmental Science and Pollution Research, 2017)

Restoration of areas degraded by alluvial sand mining: use of soil microbiological activity and plant biomass growth to assess evolution of restored riparian vegetation - Graziela R. Venson; Rosemeri C. Marenzi; Tito César M. Almeida; Alexandre Deschamps-Schmidt; Renan C. Testolin; Leonardo R. Rörig; Claudemir M. Radetski (Environmental Monitoring and Assessment, 2017)

Gametic and somatic embryogenesis through in vitro anther culture of different Citrus genotypes - J. C. Cardoso; A. M. Abdelgalel; B. Chiancone; R. R. Latado; O. Lain; R. Testolin; M. A. Germanà (Plant Biosystems, 2016)

Differentiation in DNA fingerprinting among species of the genus Acer L. in Campania (Italy) - C. Guarino; S. Santoro; L. De Simone; G. Cipriani; R. Testolin (Plant Biosystems, 2008)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Development of a new SSR-based linkage map in apricot and analysis of synteny with existing Prunus maps - L. Dondini; O. Lain; F. Geuna; R. Banfi; F. Gaiotti; S. Tartarini; D. Bassi; R. Testolin (Tree Genetics & Genomes, 2007)

Linkage maps of grapevine displaying the chromosomal locations of 420 microsatellite markers and 82 markers for R-gene candidates - G. Di Gaspero; G. Cipriani; A.-F. Adam-Blondon; R. Testolin (Theoretical and Applied Genetics, 2007)

Microsatellite and AFLP markers in the Prunus persica [L. (Batsch)] × P. ferganensis BC1 linkage map: saturation and coverage improvement - I. Verde; M. Lauria; M. T. Dettori; E. Vendramin; C. Balconi; S. Micali; Y. Wang; M. T. Marrazzo; G. Cipriani; H. Hartings; R. Testolin; A. G. Abbott; et al. (Theoretical and Applied Genetics, 2006)

Microsatellite and AFLP markers in the Prunus persica [L. (Batsch)]×P. ferganensis BC1linkage map: saturation and coverage improvement - I. Verde; M. Lauria; M. T. Dettori; E. Vendramin; C. Balconi; S. Micali; Y. Wang; M. T. Marrazzo; G. Cipriani; H. Hartings; R. Testolin; A. G. Abbott; et al. (Theoretical and Applied Genetics, 2005)

Comparative study of the discriminating capacity of RAPD, AFLP and SSR markers and of their effectiveness in establishing genetic relationships in olive - A. Belaj; Z. Satovic; G. Cipriani; L. Baldoni; R. Testolin; L. Rallo; I. Trujillo (Theoretical and Applied Genetics, 2003)

Microsatellite markers isolated in olive (Olea europaea L.) are suitable for individual fingerprinting and reveal polymorphism within ancient cultivars - G. Cipriani; M. T. Marrazzo; R. Marconi; A. Cimato; R. Testolin (Theoretical and Applied Genetics, 2002)

Embryo rescue from interspecific crosses in the genus Actinidia (kiwifruit) - A.M. Hirsch; R. Testolin; S. Brown; J. Chat; D. Fortune; J.M. Bureau; D. De Nay (Plant Cell Reports, 2001)

A kiwifruit (Actinidia spp.) linkage map based on microsatellites and integrated with AFLP markers - R. Testolin; W. G. Huang; O. Lain; R. Messina; A. Vecchione; G. Cipriani (Theoretical and Applied Genetics, 2001)

Conservation of microsatellite loci within the genus Vitis - G. Di Gaspero; E. Peterlunger; R. Testolin; K. J. Edwards; G. Cipriani (Theoretical and Applied Genetics, 2000)

AC/GT and AG/CT microsatellite repeats in peach [Prunus persica (L) Batsch]: isolation, characterisation and cross-species amplification in Prunus - G. Cipriani; G. Lot; W.-G. Huang; M. T. Marrazzo; E. Peterlunger; R. Testolin (Theoretical and Applied Genetics, 1999)

Microsatellite DNA in Actinidia chinensis: isolation, characterisation, and homology in related species - W.-G. Huang; G. Cipriani; M. Morgante; R. Testolin (Theoretical and Applied Genetics, 1998)

Restriction-site variation of PCR-amplified chloroplast DNA regions and its implication for the evolution and taxonomy of Actinidia - G. Cipriani; R. Testolin; R. Gardner (Theoretical and Applied Genetics, 1998)

Paternal inheritance of chloroplast DNA and maternal inheritance of mitochondrial DNA in the genus Actinidia - R. Testolin; G. Cipriani (Theoretical and Applied Genetics, 1997)